Cyclic behavior of RC frame members strengthened with secured CFRP sheets: comprehensive modeling strategies - Mohammed Saleem, Sama (Kansas State University, 2023)
Structural beam-column joints are critical elements in ensuring the resilience of framed structures against seismic forces. In recent years, the implementation of Fiber Reinforced Polymer (FRP) composites as strengthening materials has gained significant attention due to their remarkable mechanical properties and corrosion resistance. Further research is required to understand the behavior of frame members and joints undergoing cyclic loading when strengthened with FRP as such strengthening promotes different structural behavior of the assembly and is dominated by different failure modes. This study presents a thorough review of existing literature on the strengthening of structural beam-column joints using FRP sheets, followed by a description of a comprehensive experimental investigation and an attempt to model the cyclic lateral behavior and response of CFRP strengthened frame members aiming at enhancing our understanding of this innovative strengthening technique under seismic loading conditions. Unlike earlier studies that focused on strengthening the joint itself, this study focuses on joints reinforced in a ductile manner according to modern design codes while needing the members framing into it to be upgraded with external FRP. For this purpose, experimental data from four frame assemblies, the members of each are strengthened with FRP sheets and anchored in different configurations is used. A comparative modeling is then conducted with comparisons between the experimental data and the results predicted by the proposed model to establish the validity of the present approach. The outcomes contribute significantly to the ongoing advancements in the design and application of FRP-strengthened frame members, thereby fostering their wider implementation within the field of structural engineering.
Keywords: Seismic strengthening; CFRP fiber anchors; Frame members; Hysteresis modeling; Backbone curve; Cyclic loading